The Effect of Belimbing Wuluh (Averrhoa Bilimbi L.) and Red Guava (Psidium Guajava L.) Extract on Fasting Blood Glucose Levels of Diabetic Wistar Rats Model - Yesi Warisman; Arinda Lironika Suryana; Zora Olivia (Journal of Agromedicine and Medical Sciences, 2019)
Diabetes mellitus is a metabolic disease with special characteristic which increased blood glucose level (hiperglicemic), its happens because of the abnormality of insulin secretion, insulin mechanisme or both of them. Belimbing wuluh and red guava extract can become alternative functional drink that contain rich of vitamin C to help controlling blood glucose level. The aimed of this study was to determined the effect of belimbing wuluh and red guava extract on blood glucose levels of Rattus novergicus strain Wistar diabetic model. This research was an true experimental study with a randomized post-test control group design. Twentyfour (24) male wistar strain rats weighing 200-250 grams, aged 2-3 months, were divided into 4 groups. The control group (K-) non-diabetic rats, the control group (K+) diabetic rats given standard diet, and the treatment group diabetic rats given standard diet and belimbing wuluh and red guava extract intervetion doses 10,7 ml/day (P1) and 21ml/day (P2). Measurement of pretest posttest fasting blood glucose levels was carried out using biolyzer. The data were analyzed by One Way Anova test. The results showed that there were significant differences in delta pretest and posttest fasting blood glucose levels between all groups. Blood glucose levels decreased at 55.6%. In conclusion, belimbing wuluh and red guava extract 21ml/day most effectively decreased fasting blood glucose levels in diabetic wistar rats moldel. Keywords: belimbing wuluh, blood glucose level, diabetes mellitus, red guava